Development of medical aptitude amongst fresh medical entrants by way of relevant teaching learning sessions:a cross sectional pre-post study - Rawat, Ranu; Singh, Parmal (International Journal Of Community Medicine And Public Health, 2021)
Background: Medical Science is still one of the most sought after professions. The possession of an aptitude for the profession is a pre requisite, considering its strenuous demands from the candidate. Presently, there is no mechanism in place in India to assess aptitude in students prior to medical college entry. The aims and objectives of the study were to assess the baseline medical aptitude in the new medical entrants, to Introduce Teaching Learning Sessions for Development of Medical Aptitude in new Medical Entrants, to assess the post T/L session medical aptitude in the new medical entrants. Methods: A cross sectional, one group pre- post study was undertaken amongst 150 fresh MBBS students of Adesh Medical College and Hospital, Shahabad, after approval from the IEC. A pre-tested and pre-validated semi-structured questionnaire was used for data collection both at baseline and after relevant Teaching learning sessions. Data collected was analyzed by using Statistical package for social sciences (SPSS) Version 21. Results: The overall mean aptitude value before and after the T/L session was 102.98±8.47 and 114.51±8.60 respectively (p<0.001). Also, there was increase in the proportion of students having average and above average aptitude and decline in those having below average aptitude in the post T/L sessions as compared to the baseline levels. Conclusions: It can be concluded that medical aptitude can be built up in the new medical entrants by making them aware about it through well crafted teaching learning sessions.